Synthetic RNA Silencing in Bacteria – Antimicrobial Discovery and Resistance Breaking - Stach, James E.; Good, Liam (Frontiers in Microbiology, 2011)
The increasing incidence and prevalence of antibiotic resistance in bacteria threatens the “antibiotic miracle”. Conventional antimicrobial drug development has failed to replace the armamentarium needed to combat this problem, and novel solutions are urgently required. Here we review both natural and synthetic RNA silencing and its potential to provide new antibacterials through improved target selection, evaluation and screening. Furthermore, we focus on synthetic RNA silencers as a novel class of antibacterials and review their unique properties.